Crisphead lettuce under influence of soil conditioner, organic fertilizers and liming - Marchi, Edilene Carvalho Santos; Marchi, Giuliano; Silva, Carlos Alberto; Alvarenga, Marco Antônio Rezende (Comunicata Scientiae, 2015)
Lettuce is considered the main leafy vegetable crop in Brazil. High amounts of mineral and organic fertilizers are applied to soils during lettuce growth. There is a need of data concerning the effect of organic fertilizers and liming, including soil conditioners. Few studies were carried out verifying effects of soil conditioners, organic fertilizers and liming on lettuce production. The aim of this work was to test a soil conditioner composed of humic material, organic fertilizers and liming on “iceberg” lettuce production. The experiment was conducted at Federal University of Lavras, Minas Gerais State, Brazil, from March to July, in greenhouse conditions. The experimental design was completely randomized in a factorial scheme 5x3x2. Five doses of soil conditioner (0, 20, 40, 100, 200 L ha-1), 3 types of fertilizers (organic compost, chicken manure and mineral), with or without liming were studied. Fresh and dried biomass, commercial fresh and dried biomass, plants height, circumference of lettuce head, number of leaves, and dried root weight yield were evaluated. Chicken manure rendered the higher lettuce shoot commercial fresh weight and circumference than the other evaluated fertilizers. In general the soil conditioner did not influence lettuce production. The use of liming was very important on lettuce production when mineral fertilizers were used.